Reasons Internalism and the function of normative reasons - Sinclair, Neil (Wiely, 2017)
What is the connection between reasons and motives? According to Reasons Internalism there is a non-trivial conceptual connection between normative reasons and the possibility of rationally accessing relevant motivation. Reasons Internalism is attractive insofar as it captures the thought that reasons are for reasoning with and repulsive insofar as it fails to generate sufficient critical distance between reasons and motives. Rather than directly adjudicate this dispute, I extract from it two generally accepted desiderata on theories of normative reasons and argue that a new theory can satisfy both. The new theory locates part of the meaning of normative reason statements in their role in normative discussion. It generates a view of the connection between reasons and motives that is distinct from Reasons Internalism, yet distinctively in its spirit.